Enhancing and Capturing More Value from the Caribbean Community's Value Chains - Charles, Don. (Newcastle-upon-Tyne : Cambridge Scholars Publisher, 2019)
The organization of production processes into a chain of production stages that could be located in different countries, each of which provide a unique advantage, has become a defining characteristic of international trade. Industrial development, the movement of intermediate products, and the trading of final goods and services are inextricably linked to global value chains. Global value chain analysis is useful in providing a comprehensive overview of an entire industry, identifying an individual firm or country's position in the global value chain, and mapping how the firm or country may upgrade to capture more value along this value chain. This book presents various case studies which analyse some of the prevalent constraints experienced in industries of the Caribbean Community (CARICOM) member states. In addition, it identifies practical policy recommendations which can be used to address such challenges, and allow the member states to capture more value from their industries' global value chains. It addresses issues such as the declining preferences in agriculture value chains, the feasibility of enhancing the economic contribution of the maritime industry, the urgency for climate-resilient strategies in the banana industry, and the need for local content policy to create an appropriate framework to capture a fair share of value from the hydrocarbon industry. Given the persistence of challenges, the lack of upgrading, and the dearth of research conducted on value chains in the CARICOM region, this book can serve as a basis upon which governments and regional organizations may adopt policy recommendations to address trade and investment-related challenges, and increase the member states' effective participation in international trade.
Intro -- Table of Contents -- Chapter One -- Chapter Two -- Chapter Three -- Chapter Four -- Chapter Five -- Chapter Six -- Chapter Seven -- Chapter Eight.
Descripción basada en metadatos suministrados por el editor y otras fuentes.
Recurso electrónico. Santa Fe, Arg.: elibro, 2019. Disponible vía World Wide Web. El acceso puede estar limitado para las bibliotecas afiliadas a elibro.
Keywords: Value analysis (Cost control); Value distribution theory; Análisis de valor (control de costos); Teoría de la distribución del valor; Libros electrónicos.